Gambaran Resiliensi Masyarakat Aceh Setelah Mengalami Pengalaman Traumatis - Nur Afni Safarina; Ella Suzanna (Jurnal Psikologi Terapan, 2020)
Aceh is one of the many areas affected by the disaster. In recent years, Aceh has caught the attention of most countries in the world because Aceh has just passed two major human tragedies. The first tragedy was the 30-year political conflict between the Government of Indonesia and the Free Aceh Movement (GAM), while the second human tragedy included the earthquake and tsunami disaster on 26 December 2004. There were many different responses to disaster management. Most children who survive have strong feelings after a traumatic event but recover from trauma; others have more difficulty recovering and will need additional assistance. The children who were exposed to traumatic experiences about 15 years ago are now adults. The hope is that these adult children will no longer experience trauma and be able to deal with problems properly. Therefore, this study attempts to investigate what factors influence the ability of the Acehnese people to recover and rise from traumatic experiences. The ability that an individual has to 'bounce back' from traumatic experiences is known as the resilience factor. Furthermore, in this study, the researcher intends to analyze not only how individuals cope with traumatic experiences, but also how they grow and develop after exposure to psychological trauma.